A NEUROLINGUISTIC APPROACH TO ADDRESSING STUDENTS’ DIFFICULTIES IN ARABIC MORPHOLOGY (SHOROF) : A CASE STUDY AT STAINU KOTABUMI LAMPUNG - Nurul Fadlilah; Muhammad Jafar Shodiq; Puji Rahayu (Jurnal Konseling Pendidikan Islam, 2026)
This study aims to examine the application of a neurolinguistic approach in overcoming students' difficulties in shorof learning at STAINU Kotabumi. Students encounter significant challenges in memorizing, recognizing derivation patterns, and applying Arabic morphological rules, particularly tashrif patterns, in their daily speaking and writing practices. This study employs a qualitative case study design, with Arabic shorof lecturers and students enrolled in shorof courses serving as informants. Data were collected through classroom observation and in-depth interviews, then analyzed using thematic analysis techniques. The findings reveal that the neurolinguistic approach assists students in comprehending shorof learning through the optimization of brain functions in language processing. The reinforcement of the nervous system in linguistic aspects is capable of integrating the brain's role in shorof learning across cognitive, affective, and psychomotor dimensions. The application of neurolinguistic strategies, including multi-sensory learning techniques and repetition-based memory reinforcement, proved effective in facilitating students' mastery of tashrif patterns while simultaneously enhancing their motivation and active engagement throughout the learning process. Thus, the neurolinguistic approach as a pedagogical alternative in Arabic morphology learning is capable of maximizing students' potential through the optimization of brain functions. This approach has broad implications for the development of Arabic language learning in Islamic higher education, particularly in strengthening shorof studies in a more systematic and sustainable manner.